Physical Fitness of Six and Seven-Year Old Children and Its Environmental Determinants - Cieśla, Elżbieta (INSTED: Interdisciplinary Studies in Education & Society, 2012)
Currently it is acknowledged that rural environment, inadequately to possessed natural conditions, creates worse standards for the development of general physical fitness of both examined girls and boys compared to what the urban environment offers. In turn, children raised in the city, have a relatively low level of various aspects of strength and stamina. It can be also assumed that both mentioned environments shape different fitness profiles. In this article I will try to verify a hypothesis which assumes a diversified level of motoric fitness of a child in the pre-school age depending on the place of residence as well as on the educational institution. Alternatively, it can be assumed that, in comparison to the rural environment, the fitness level of children from the urban environment will be higher and the children who attend kindergarten will be fitter than those who fulfil the compulsory schooling obligation at school.